Social representations by gender on ambiental management and pollution of the coastal coast of Yunguyo, Puno - Tumi Quispe, Jesús E. (2020)
The study aimed to determine the level of knowledge that the population possesses by gender about environmental management and pollution of the coastal coastline of the city of Yunguyo-Puno. The research is non-experimental, quantitative and transversal; Descriptive and correlational character, the analysis dimension was social and environmental and micro level. The information was obtained through a structured survey applied to the urban population of Yunguyo. The results were: The level of knowledge that the majority of the urban population of Yunguyo possesses about environmental management and pollution of the city's coastal coastline is poor, but differentiated by gender; situation that based on statistical evidence denotes that the level of knowledge that women possess is higher not only by socio-economic status, but also by the perceptions they have on sanitation and environmental education, as well as on the effects of contamination of the inner bay in human health and due to the conditions of access to information provided by the regional and local environmental institutions.